Moving Load Robot Using Wifi Network and Android Based - Irawan, Yuda (Universitas Muhammadiyah Yogyakarta, 2021)
A robot is a mechanical device that can perform physical tasks, either using human supervision or control by using predefined programs. In this research, a robot prototype will be designed that can move goods in the form of glasses and plates from one place to another using controls from Android. This system or robot can work as expected, the system is capable of mapping based on the path that has been made. The method used in developing this robot is the prototype method so that the robot is built according to the needs that the user wants directly and can be revised according to the user's wishes after making the design. The robot is also able to take a glass / plate from the table to move it to the desired place. From the experiments that have been carried out as many as 10 times on the movement of the robot to move glasses and plates, the research got a value of 50% perfect success rate, 30% who failed in the middle of the road, and 20% who failed to do the mapping of all the series of experiments that must be passed.